2011
DOI: 10.1097/phh.0b013e3181df7f6c
|View full text |Cite
|
Sign up to set email alerts
|

Continued Benefits of a Technical Assistance Web Site to Local Tobacco Control Coalitions During a State Budget Shortfall

Abstract: The Enhanced Web site may have had a protective effect on defunded coalitions. Defunded coalitions may have increased their capacity by using the Enhanced Web site when fully funded or by continuing to use the available online resources after defunding. Web-based technical assistance with online training and resources may be a good investment when future funding is not ensured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Originally, coalitions had been pair matched on population characteristics and type of lead agency, but defunding broke several of the matched pairs. Analyses reported elsewhere showed that defunding appeared to affect the performance of coalitions assigned to the Basic website more than those assigned to the Enhanced website (Buller et al, 2011).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Originally, coalitions had been pair matched on population characteristics and type of lead agency, but defunding broke several of the matched pairs. Analyses reported elsewhere showed that defunding appeared to affect the performance of coalitions assigned to the Basic website more than those assigned to the Enhanced website (Buller et al, 2011).…”
Section: Methodsmentioning
confidence: 92%
“…Also, the Enhanced website had better communication tools than did the Basic website which enabled coalition leaders and members to obtain support from state tobacco control professionals and exchange ideas and experiences with other local coalitions. Not surprisingly given its additional content, interactivity, and deep structure, the Enhanced website was used more by coalitions than the Basic website (Buller et al, 2011).…”
Section: > > Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with conceptual models suggesting coalition functioning has an important influence on a coalition’s ability to support program implementation (e.g., Brown, et al, 2012). Thus, our findings point to the importance of training and technical assistance efforts, which can improve coalition functioning (Buller et al, 2011; Feinberg, et al, 2002; Feinberg, Ridenour, et al, 2008; Riggs, Nakawatase, & Pentz, 2008). However, technical assistance may be most effective when it focuses on those aspects of coalition functioning that are most important for coalition outcomes, as not all coalition functioning characteristics equally predicted support for program implementation.…”
Section: Discussionmentioning
confidence: 69%